Lignite-based supercapacitor active carbon electrode material and preparation method thereof

Through the pretreatment and alkaline activation process optimization of lignite, the problems of activated carbon structural instability and toxic activator in chemical activation method are solved, and the preparation of supercapacitor electrode materials with high specific surface area and cycle stability are achieved, which improves energy Utilization efficiency and environmental friendliness.

CN119296990APending Publication Date: 2025-01-10NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411728845.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, chemical activation method has problems with the uneven reaction of alkaline activator and the use of toxic activator when preparing supercapacitor activated carbon, which affects the structural stability and performance of activated carbon.

Method used

Pretreat lignite with hydrochloric acid, hydrofluoric acid and calcium phosphate solutions, combined with alkaline activator and deionized water, optimize the activation process to form activated carbon electrode materials with high specific surface area and suitable pore structures by strictly controlling the sintering temperature and time. .

Benefits of technology

The power density and cycle stability of the supercapacitor are improved, environmental pollution is reduced, and high-performance and low-cost carbon electrode materials are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296990A_ABST
    Figure CN119296990A_ABST
Patent Text Reader

Abstract

The invention provides a lignite-based supercapacitor activated carbon electrode material and a preparation method thereof, and belongs to the technical field of electrochemical power supply material preparation. The preparation method comprises the following steps: S1, performing hydrochloric acid pickling on lignite raw coal powder for X2 hours, performing hydrofluoric acid pickling for X2 hours, and heating a calcium phosphate solution for deoxidation to obtain pretreated lignite; s2, uniformly stirring and mixing the pretreated lignite, an alkaline activator and deionized water according to the mass ratio of 1: X4: (5-10) to obtain a mixture; s3, activation is conducted, the activation temperature is X1 DEG C, and the activation time is X3 h; cooling to obtain a roasted product; s4, acid pickling with diluted hydrochloric acid; the specific capacitance of the active carbon electrode material is Y F / g, wherein Y = a + b * X1 + c * X2 + d * X3 + e * X4-f * X1 * X2 + g * X1 * X3 + h * X1 * X4 + i * X2 * X3 + j * X2 * X4 + k * X3 * X4-l * X12-m * X22-n * X32-o * X42. The preparation method is simple, the cost is low, the process repeatability is good, the prepared porous carbon has a high specific surface area, and the power density and the cycling stability of the supercapacitor are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical power source material preparation, and in particular to a lignite-based supercapacitor activated carbon electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of social science and technology, energy consumption has also increased rapidly, and the resulting greenhouse gas emissions have increased exponentially, causing serious environmental problems. As a low-rank coal, lignite has a low degree of coalification, which causes a large amount of carbon dioxide, particulate matter and harmful gases to be produced during combustion, which will pollute the atmosphere and water bodies. In addition, lignite has a high water content and low calorific value, and direct combustion without treatment is extremely harmful to the environment. Therefore, it is particularly important to improve the utilization efficiency of lignite and reduce its negative impact on the environment through effective means.

[0003] At present, the treatment methods to improve the utilization rate of lignite include lignite upgrading and grading utilization technology and coal green mining and clean methods. Although lignite upgrading and grading utilization technology reduces the emission of coal-burning pollutants, its technical difficulty is relatively high and it is not easy to store and transport, which limits the application and promotion of this technology. The cost of coal green mining and clean technology is relatively high and has certain environmental risks. After continuous exploration and research, it was finally found that lignite with high energy density and combustion efficiency has broad application prospects in the field of power generation.

[0004] Low-rank lignite is abundant in reserves and cheap in price. It can generate high-performance activated carbon during the activation process. It has the characteristics of low carbon content, high storage capacity and high moisture content. By converting lignite into activated carbon electrode sheets and applying them to the field of electrochemical energy storage, such as carbon electrodes for supercapacitors, it can not only improve energy utilization efficiency, but also reduce direct environmental pollution to a certain extent. This process of conversion and application has promoted the development of the energy storage field and has positive significance for the optimization of energy structure and the improvement of the environment.

[0005] Activated carbon, as a porous carbon material, is currently a widely used supercapacitor electrode material. Lignite-based activated carbon is suitable for supercapacitor applications due to its high specific surface area and good electrical conductivity. After physical or chemical activation, lignite is converted into activated carbon with a porous structure. The large number of tiny pores inside the porous structure provide more specific surface area. These pore structures greatly increase the effective surface area, which helps to form a double layer at the interface between the electrode and the electrolyte, thereby achieving efficient charge storage.

[0006] How to optimize the preparation process to improve the pore structure of activated carbon and increase its specific surface area is the focus of current research. Carbon electrode materials with suitable pore structures can provide more active sites, thereby improving the conductivity of electrolyte ions and further enhancing capacitance performance. Therefore, lignite-based activated carbon shows great development potential as a supercapacitor electrode material.

[0007] Chemical activation is one of the commonly used methods for preparing high-quality porous carbon. It is a single-step technology for producing activated carbon. Compared with the physical activation method, the chemical activation method also has the advantages of fast activation time, relatively higher carbon yield, larger specific surface area and porosity. Under the action of chemical activators, it is relatively easy to construct a porous structure during the activation process. At present, the activators widely used in the chemical activation process include acidic activators, alkaline activators and neutral activators. Among them, acidic activators have the risk of corroding equipment and have poor activation effects; neutral activators have high costs, and the activators and their derivatives are toxic, which limits their application.

[0008] Compared with acidic activators and neutral activators, alkaline activators not only have better activation effects, but also avoid the hazards of toxic properties to a large extent. The formation of pore structure is a key step in the preparation process of activated carbon. When using alkaline activators for activation, the unevenness of the chemical reaction during the activation process or the incomplete reaction between the activator and the raw material will lead to problems such as unstable activated carbon structure, which affects the performance and application effect of activated carbon. In response to the above problems, the present invention optimizes the preparation process and successfully prepares coal-based activated carbon with suitable pore structure and high specific surface area, further promoting the development of supercapacitors in the field of electrochemistry. Summary of the invention

[0009] In view of the problems existing in the prior art, the present invention provides a lignite-based supercapacitor activated carbon electrode material and a preparation method thereof. The preparation method of the present invention is simple and low in cost. The prepared porous carbon has a high specific surface area, which improves the power density and cycle stability of the supercapacitor, and has great practical significance for promoting the optimization of the energy structure and the improvement of the environment.

[0010] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0011] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0012] S1. The raw lignite powder is pickled with hydrochloric acid at a concentration of 1-5 mol / L for X2 h, and then washed with water and dried; then pickled with hydrofluoric acid at a concentration of 5-30wt% for X2 h, and then washed with water and dried; then heated and deoxidized with a calcium phosphate solution at a concentration of 1-2 mol / L, and then washed with water and dried to obtain pretreated lignite;

[0013] S2, stirring and mixing the pretreated lignite, alkaline activator and deionized water in a mass ratio of 1:X4:5-10 to obtain a mixture;

[0014] S3, activating the mixture under an inert atmosphere at a temperature of X1°C and an activation time of X3 h; then cooling the mixture to room temperature to obtain a calcined product;

[0015] S4, washing the calcined product with dilute hydrochloric acid, washing with water, and drying to obtain the lignite-based supercapacitor activated carbon electrode material;

[0016] The specific capacitance of the lignite-based supercapacitor activated carbon electrode material is YF / g, and the following relationship is obtained by fitting Y with X1, X2, X3 and X4:

[0017] Y=a+b·X1+c·X2+d·X3+e·X4–f·X1·X2+g·X1·X3+h·X1·X4+i·X2·X3+j·X2·X4+k·X3·X4

[0018] –l·X1 2 –m·X2 2 –n·X3 2 –o·X4 2 ;

[0019] Among them, -12498.70833≤a≤-8849.075, 15.54675≤b≤24.2525, 0≤c≤74.67875,

[0020] 305.425≤d≤841.425,821.57333≤e≤1312.7,-0.001167≤f≤0.02375,

[0021] -0.109≤g≤0.243, -0.224≤h≤0.11, -0.81667≤i≤0.6125, -3.825≤j≤0.62917,

[0022] -49.5≤k≤0.2, 0.01086≤l≤0.016075, 0≤m≤0.80698, 40.42≤n≤138.6,

[0023] 42.17667≤o≤177.5;650≤X1≤900,20≤X2≤28,0.5≤X3≤3.5,2≤X4≤7.5.

[0024] This formula is obtained by taking a series of orthogonal single-factor experiments as premise and then simulating them through response surface experimental method to predict the response level of a given factor.

[0025] In the above preparation method, hydrochloric acid pickling removes inorganic minerals in lignite, such as silicon, aluminum, iron, etc., thereby improving the combustion efficiency of lignite; hydrofluoric acid pickling removes organic impurities in lignite, such as humus, lignin, etc., thereby further improving the purity and reactivity of lignite; calcium phosphate can remove oxides and oxygen element impurities in pickled lignite, improve the performance and stability of the material, thereby improving the conductivity and reactivity of the material; finally, the acidic substances and phosphates in the lignite are removed by washing with deionized water to reduce corrosion to subsequent processing equipment, thereby obtaining high-purity oxygen-free lignite.

[0026] In the process of mixing pretreated lignite with alkaline activator, deionized water as a solvent can promote sufficient contact and mixing between the reactants, ensuring that the activator can evenly penetrate into every part of the lignite, thereby improving the reaction efficiency; at the same time, the amount of deionized water added directly affects the pore structure of activated carbon. An appropriate amount of deionized water helps to form more micropores and mesopores, and too much or too little water may lead to unstable pore structure.

[0027] In the above process, the sintering temperature is set between 650-900℃, which is based on the optimal temperature range of the pyrolysis and activation process of the volatile matter in the lignite; within this temperature range, the volatile matter in the lignite can be fully released to form a rich pore structure, thereby increasing the specific surface area. When the sintering temperature is lower than 650℃, the volatile matter in the lignite may not be fully released, resulting in an underdeveloped pore structure and a smaller specific surface area; when the sintering temperature is higher than 900℃, the excessively high temperature may cause the already formed pore structure to collapse or merge, resulting in a reduction in the specific surface area. The holding time is set between 0.5-3.5h, which is based on the time required for the lignite to fully react at high temperature and form a stable pore structure; within this time range, the volatile matter in the lignite can be fully released and react with the alkaline activator to form a stable pore structure.

[0028] Preferably, the alkaline activator is one of KOH, NaOH, K2CO3, and Na2CO3.

[0029] Preferably, when the alkaline activator is KOH, Y=-12498.70833+24.2525X1+74.67875X2–505.95333X3+905.95X4–0.02375X1·X2+0.61X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X12 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , among which, 700≤X1≤800, 20≤X2≤28, 1.5≤X3≤2.5, 4.5≤X4≤5.5.

[0030] Preferably, when the alkaline activator is NaOH, Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X1·X2+0.243X1·X3–0.224X1·X4–0.816667X2·X3+0.629167X2·X4–49.5X3·X4–0.014203X1 2 –0.13876X2 2 –82.67667X3 2 –42.17667X4 2 , among which, 750≤X1≤850, 20≤X2≤28, 0.5≤X3≤1.5, 6.5≤X4≤7.5.

[0031] Preferably, when the alkaline activator is K2CO3, Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2 , where 650≤X1≤750, X2=24, 2.5≤X3≤3.5, 2≤X4≤4.

[0032] Preferably, when the alkaline activator is Na2CO3, Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4+0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where 800≤X1≤900, X2=24h, 2≤X3≤3, 3.5≤X4≤4.5.

[0033] For each alkaline activator, further optimizing the sintering temperature and holding time according to the properties of the alkaline activator helps to promote the full release of volatiles in lignite and the formation of a stable pore structure, thereby increasing its specific surface area.

[0034] Preferably, in step S1, the method for preparing the raw lignite powder comprises the following steps: crushing, grinding and sieving the lignite to obtain the raw lignite powder; the lignite is Hebei Lingshou lignite; the ash content of the lignite is 27-30%. The minerals in the lignite can serve as a template during the activation process to help form more and more stable pore structures, thereby increasing the specific surface area and porosity of the activated carbon.

[0035] Preferably, in step S1, the heating temperature of the heating deoxidation is 60-80°C, and the deoxidation time is 20-28h. At this temperature, possible excessive carbonization or material structure damage is avoided, thereby maintaining the integrity of the material. Within this time range, it is ensured that the calcium phosphate solution has enough time to contact and react with the oxygen element in the lignite, thereby improving the deoxidation efficiency. If the time is too short, the reaction may not be complete and the oxygen removal may not be thorough.

[0036] Preferably, in step S3, the inert gas is nitrogen or argon; and the temperature is raised to X1°C at a heating rate of 2-5°C / min; in this sintering process, an appropriate heating rate ensures uniform temperature distribution inside the material, facilitates sufficient contact between reactants, and promotes uniform reaction;

[0037] In step S4, the dilute hydrochloric acid pickling is carried out using hydrochloric acid with a concentration of 1-2 mol / L, and the pickling time is 2-5 hours. Pickling again after sintering and activation can remove impurities and improve the purity and application effect of the activated carbon.

[0038] As a general inventive concept, the present invention also provides a lignite-based supercapacitor activated carbon electrode material prepared by the above preparation method.

[0039] The beneficial technical effects of the present invention are:

[0040] 1. The present invention uses low-rank lignite as the main raw material, and synthesizes lignite-based activated carbon materials by chemical activation method, and the lignite-based activated carbon materials can be used in the field of electrochemical energy storage. The preparation process of the present invention is simple, and the power density and cycle stability of supercapacitors are improved. At the same time, the reserves of raw materials are huge, the price is low and the sources are wide.

[0041] 2. The present invention strictly controls the process parameters such as sintering temperature, time, pickling time, etc., and selects a suitable and appropriate amount of alkaline activator and deionized water to mix with the pretreated lignite. Through this preparation process, an activated carbon electrode material with a high specific surface area and a suitable pore structure can be prepared to ensure the performance advantages of the supercapacitor, and the utilization efficiency of the lignite can be improved, and its negative impact on the environment can be reduced, thereby obtaining a carbon electrode material with good market potential and comprehensive performance.

[0042] 3. The present invention uses hydrochloric acid, hydrofluoric acid and calcium phosphate solution to pre-treat lignite in sequence, and through acid washing and deoxidation treatment, the ash and oxygen content in the lignite are effectively reduced, which helps to adjust the pore size distribution and surface chemical properties of the activated carbon. The deashed lignite provides more contact surface for the alkaline activator, which promotes the development and uniform distribution of the activated carbon pores. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 This is a process flow chart of the present invention for preparing lignite-based supercapacitor activated carbon electrode materials;

[0045] Figure 2 is the XRD pattern of the lignite-based supercapacitor activated carbon electrode material in Example 1;

[0046] Figure 3 is a SEM morphology of the lignite-based supercapacitor activated carbon electrode material in Example 1;

[0047] Figure 4 is a nitrogen adsorption-desorption isotherm graph of the lignite-based supercapacitor activated carbon electrode material in Example 1;

[0048] Figure 5 is a pore size distribution diagram of the lignite-based supercapacitor activated carbon electrode material in Example 1;

[0049] Figure 6 This is a scatter plot comparing the predicted value of the formula and the actual value when the activating agent is KOH;

[0050] Figure 7 This is a scatter plot comparing the predicted value of the formula and the actual value when the activating agent is NaOH;

[0051] Figure 8 This is a scatter plot comparing the predicted value of the formula and the actual value when the activating agent is K2CO3;

[0052] Fig. 9 This is a scatter plot comparing the predicted value of the formula and the actual value when the activating agent is Na2CO3;

[0053] Fig.10 This is a long cycle performance test chart of the lignite-based supercapacitor activated carbon electrode material in Example 1 at a current density of 10 A / g. DETAILED DESCRIPTION

[0054] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The lignite used in the examples and comparative examples is Hebei Lingshou lignite, and the performance indicators of the lignite are shown in Table 1. Other raw materials are commercially available and have an analytical purity.

[0056] Table 1

[0057] Full moisture Analyze moisture Total sulfur Ash Volatile Matter Fixed Carbon Coke slag characteristics symbol Mt% Mad% St.d% <![CDATA[A ad %]]> <![CDATA[V ad %]]> <![CDATA[FC ad %]]> CRC(1-8) Detection value 1.48 0.95 3.70 28.36 28.74 41.95 5

[0058] The performance test methods used are:

[0059] 1. X-ray diffraction analysis (XRD): XRD analysis was performed using a DX2500 X-Ray diffractometer to determine the crystalline phase composition of the coal-based activated carbon material.

[0060] 2. Scanning electron microscopy (SEM): A ZEISS SUPRA55 field emission scanning electron microscope was used to determine the morphology and structure of the activated carbon electrode material samples.

[0061] 3. Adsorption isotherm analysis: The adsorption-desorption isotherm curve of the activated carbon electrode material was analyzed in the relative pressure range of 0.05-1 using an SSA-4000 adsorption-desorption instrument.

[0062] Specific surface area calculation:

[0063]

[0064] In the formula, S BET ——Specific surface area, m 2 / g;

[0065] ρ——Material density, g / cm 3 or kg / m 3 ;

[0066] d——pore diameter, nm or m.

[0067] 4. Pore structure analysis: The Barrett, Joyner, Halenda (BJH) model and micropore distribution (MP) model are used to analyze the pore size distribution of activated carbon electrode materials. Porosity calculation:

[0068] In the formula, ∈——porosity;

[0069] V P——pore volume, cm 3 or m 3 ;

[0070] V t ——Total volume, cm 3 or m 3 .

[0071] 5. Electrochemical test: Use CHI660E electrochemical workstation to analyze and test the specific capacitance of the activated carbon electrode.

[0072] (1) Capacitance calculation:

[0073] Where, C——capacitance, F (farad);

[0074] I——current, A (ampere);

[0075] Δt——Charge and discharge time, s (seconds);

[0076] ΔV – voltage change, V (volts).

[0077] (2) Capacitance retention rate:

[0078] In the formula, C n ——Capacitance value measured after n cycles, F (farad);

[0079] C0——initial capacitance value, F (farad).

[0080] (3) Coulomb efficiency:

[0081] In the formula, Q 放电 ——The charge extracted during the discharge process, C (coulomb) or Ah (ampere-hour);

[0082] Q 充电 ——The charge input during the charging process, C (coulomb) or Ah (ampere-hour).

[0083] Embodiment 1:

[0084] A method for preparing a lignite-based supercapacitor activated carbon electrode material, referring to Figure 1 The process flow chart provided, the preparation method comprises the following steps:

[0085] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0086] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0087] S3, stirring and mixing the pretreated lignite, alkaline activator KOH, and deionized water in a mass ratio of 1:X4:8, X4=5, to obtain a mixture;

[0088] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750 and X3=2; then cooling it to room temperature with the furnace to obtain a calcined product;

[0089] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain a lignite-based supercapacitor activated carbon electrode material (lignite-based activated carbon).

[0090] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0091] Y=-12498.70833+24.2525X1+74.67875X2+505.95333X3+905.95X4–0.02375X1·

[0092] X2+0.061X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X1 2 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , where X1=750, X2=24, X3=2, X4=5.

[0093] The XRD pattern of the lignite-based supercapacitor activated carbon electrode material prepared in Example 1 is as follows: Figure 2As shown, there are two obvious diffraction peaks in the coal-based activated carbon, corresponding to the (002) and (100) crystal plane diffraction of the disordered carbon structure, indicating that it has an amorphous and highly disordered structure.

[0094] The morphology of activated carbon electrode materials is as follows Figure 3 As shown in Figure 2, after chemical activation treatment, the raw coal produces a rich pore structure. Its adsorption-desorption isotherm curve and pore structure analysis are shown in Figure 2. Figure 4 , 5 As shown in the figure, it can be seen that the sample shows the combined characteristics of type I isotherm (microporous and mesoporous materials) and H3 type hysteresis loop (0.5-1.0P / P0), indicating the presence of a large number of micropores and mesopores. In the relative pressure range of 0.4-1.0, the curve trend is relatively gentle, the nitrogen adsorption rate is slow, and there are a large number of mesopores; in the relative pressure range of 0.8-1.0, the adsorption and desorption curve has a slightly steep trend, which indicates that there are also large pores. Suitable pore structure and high specific surface area can provide more active sites, thereby increasing the effective formation area of ​​the double electric layer, and further effectively improving the electrochemical performance of the supercapacitor.

[0095] Embodiment 2:

[0096] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0097] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0098] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0099] S3, stirring and mixing the pretreated lignite, alkaline activator NaOH, and deionized water in a mass ratio of 1:X4:8, X4=7, to obtain a mixture;

[0100] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min in an argon atmosphere for activation, and activating it for X3 h, where X1=800 and X3=1; then cooling it to room temperature in the furnace to obtain a calcined product;

[0101] S5. The calcined product is pickled with 2 mol / L dilute hydrochloric acid for 2 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain a lignite-based supercapacitor activated carbon electrode material.

[0102] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0103] Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X

[0104] 1.X2+0.243X1.X3–0.224X1.X4–0.816667X2.X3+0.629167X2.X4–49.5X3. 2 –0.13876X2 2 –82.67667X3 2 –42.17667X4 2 , where X1=800, X2=24, X3=1, X4=7.

[0105] Embodiment 3:

[0106] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0107] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0108] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0109] S3, stirring and mixing the pretreated lignite, alkaline activator K2CO3 and deionized water in a mass ratio of 1:X4:8, X4=3.5, to obtain a mixture;

[0110] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=700 and X3=3; then cooling it to room temperature with the furnace to obtain a calcined product;

[0111] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 5 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain a lignite-based supercapacitor activated carbon electrode material.

[0112] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0113] Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5

[0114] X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2 , where X1=700, X2=24, X3=3, X4=3.5.

[0115] Embodiment 4:

[0116] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0117] S1, crushing and grinding the lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0118] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0119] S3, stirring and mixing the pretreated lignite, alkaline activator Na2CO3 and deionized water in a mass ratio of 1:X4:8, X4=4, to obtain a mixture;

[0120] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min in an argon atmosphere for activation, and activating it for X3 h, where X1=850 and X3=2.5; then cooling it to room temperature in the furnace to obtain a calcined product;

[0121] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3.5 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain a lignite-based supercapacitor activated carbon electrode material.

[0122] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0123] Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4

[0124] +0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where X1=850, X2=24, X3=2.5, X4=4.

[0125] Embodiment 5:

[0126] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0127] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0128] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=28, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=28, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 28 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0129] S3, stirring and mixing the pretreated lignite, alkaline activator KOH, and deionized water in a mass ratio of 1:X4:8, X4=4.5, to obtain a mixture;

[0130] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750 and X3=2; then cooling it to room temperature with the furnace to obtain a calcined product;

[0131] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0132] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0133] Y=-12498.70833+24.2525X1+74.67875X2+505.95333X3+905.95X4–0.02375X1·

[0134] X2+0.061X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X1 2 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , where X1=750, X2=28, X3=2, X4=4.5.

[0135] Embodiment 6:

[0136] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0137] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0138] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=28, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=28, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated with a phosphoric acid solution at a concentration of 2 mol / L for calcium deoxidation, the heating temperature was 70°C, the deoxidation time was 28 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0139] S3, stirring and mixing the pretreated lignite, alkaline activator KOH, and deionized water in a mass ratio of 1:X4:8, X4=5, to obtain a mixture;

[0140] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=800 and X3=2; then cooling it to room temperature with the furnace to obtain a calcined product;

[0141] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0142] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0143] Y=-12498.70833+24.2525X1+74.67875X2+505.95333X3+905.95X4–0.02375X1·

[0144] X2+0.061X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X1 2 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , where X1=800, X2=28, X3=2, X4=5.

[0145] Embodiment 7:

[0146] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0147] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0148] S2, the lignite raw coal powder is pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time is X2 h, X2=20, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time is X2 h, X2=20, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated with a phosphoric acid solution at a concentration of 2 mol / L for calcium deoxidation, the heating temperature is 70°C, the deoxidation time is 20 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0149] S3, stirring and mixing the pretreated lignite, alkaline activator KOH, and deionized water in a mass ratio of 1:X4:8, X4=5, to obtain a mixture;

[0150] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=700 and X3=2; then cooling it to room temperature with the furnace to obtain a calcined product;

[0151] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0152] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0153] Y=-12498.70833+24.2525X1+74.67875X2+505.95333X3+905.95X4–0.02375X1·

[0154] X2+0.061X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X1 2 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , where X1=700, X2=20, X3=2, X4=5.

[0155] Embodiment 8:

[0156] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0157] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0158] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=20, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=20, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 20 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0159] S3, stirring and mixing the pretreated lignite, alkaline activator NaOH, and deionized water in a mass ratio of 1:X4:8, X4=7.5, to obtain a mixture;

[0160] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min in an argon atmosphere for activation, and activating it for X3 h, where X1=800 and X3=1; then cooling it to room temperature in the furnace to obtain a calcined product;

[0161] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0162] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0163] Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X

[0164] 1.X2+0.243X1.X3–0.224X1.X4–0.816667X2.X3+0.629167X2.X4–49.5X3. 2 –0.13876X2 2 –82.67667X3 2 –42.17667X4 2 , where X1=800, X2=20, X3=1, X4=7.5.

[0165] Embodiment 9:

[0166] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0167] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0168] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0169] S3, stirring and mixing the pretreated lignite, alkaline activator NaOH, and deionized water in a mass ratio of 1:X4:8, X4=7, to obtain a mixture;

[0170] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=850 and X3=1.5; then cooling it to room temperature with the furnace to obtain a calcined product;

[0171] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0172] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0173] Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X

[0174] 1.X2+0.243X1.X3–0.224X1.X4–0.816667X2.X3+0.629167X2.X4–49.5X3. 2 –0.13876X2 2 –82.67667X3 2 –42.17667X4 2 , where X1=850, X2=24, X3=1.5, X4=7.

[0175] Embodiment 10:

[0176] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0177] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0178] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0179] S3, stirring and mixing the pretreated lignite, alkaline activator NaOH, and deionized water in a mass ratio of 1:X4:8, X4=7, to obtain a mixture;

[0180] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750 and X3=1.5; then cooling it to room temperature with the furnace to obtain a calcined product;

[0181] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0182] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0183] Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X

[0184] 1.X2+0.243X1.X3–0.224X1.X4–0.816667X2.X3+0.629167X2.X4–49.5X3. 2 –0.13876X2 2 –82.67667X3 2–42.17667X4 2 , where X1=750, X2=24, X3=1.5, X4=7.

[0185] Embodiment 11:

[0186] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0187] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0188] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0189] S3, stirring and mixing the pretreated lignite, alkaline activator K2CO3 and deionized water in a mass ratio of 1:X4:8, X4=3.5, to obtain a mixture;

[0190] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750 and X3=3.5; then cooling it to room temperature with the furnace to obtain a calcined product;

[0191] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0192] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0193] Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5

[0194] X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2, where X1=750, X2=24h, X3=3.5, X4=3.5.

[0195] Embodiment 12:

[0196] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0197] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0198] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0199] S3, stirring and mixing the pretreated lignite, alkaline activator K2CO3 and deionized water in a mass ratio of 1:X4:8, X4=3.5, to obtain a mixture;

[0200] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750 and X3=2.5; then cooling it to room temperature with the furnace to obtain a calcined product;

[0201] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0202] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0203] Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5

[0204] X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2, where X1=750, X2=24h, X3=2.5, X4=3.5.

[0205] Embodiment 13:

[0206] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0207] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0208] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0209] S3, stirring and mixing the pretreated lignite, alkaline activator K2CO3 and deionized water in a mass ratio of 1:X4:8, X4=4, to obtain a mixture;

[0210] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=750°C and X3=3; then cooling it to room temperature with the furnace to obtain a calcined product;

[0211] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0212] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0213] Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5

[0214] X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2 , where X1=750, X2=24h, X3=3, X4=4.

[0215] Embodiment 14:

[0216] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0217] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0218] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0219] S3, stirring and mixing the pretreated lignite, alkaline activator Na2CO3 and deionized water in a mass ratio of 1:X4:8, X4=4.5, to obtain a mixture;

[0220] S4, placing the mixed material in a tubular furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=850 and X3=3; then cooling it to room temperature with the furnace to obtain a calcined product;

[0221] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0222] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0223] Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4

[0224] +0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where X1=850, X2=24, X3=3, X4=4.5.

[0225] Embodiment 15:

[0226] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0227] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0228] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0229] S3, stirring and mixing the pretreated lignite, alkaline activator Na2CO3 and deionized water in a mass ratio of 1:X4:8, X4=4.5, to obtain a mixture;

[0230] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min for activation under an argon atmosphere, and activating it for X3 h, where X1=850 and X3=2; then cooling it to room temperature with the furnace to obtain a calcined product;

[0231] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0232] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0233] Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4

[0234] +0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where X1=850, X2=24, X3=2, X4=4.5.

[0235] Embodiment 16:

[0236] A method for preparing a lignite-based supercapacitor activated carbon electrode material comprises the following steps:

[0237] S1, crushing and grinding the lump lignite, and passing it through a 100-mesh standard sieve to obtain lignite raw coal powder;

[0238] S2, the raw lignite powder was pickled with hydrochloric acid at a concentration of 4 mol / L, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then pickled with hydrofluoric acid at a concentration of 15wt%, the pickling time was X2 h, X2=24, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h; then heated and deoxidized with a calcium phosphate solution at a concentration of 2 mol / L, the heating temperature was 70°C, the deoxidation time was 24 h, then filtered and washed with deionized water until neutral, and then dried in a 60°C drying oven for 12 h to obtain pretreated lignite;

[0239] S3, stirring and mixing the pretreated lignite, alkaline activator Na2CO3 and deionized water in a mass ratio of 1:X4:8, X4=4, to obtain a mixture;

[0240] S4, placing the mixed material in a tube furnace, heating it to X1°C at a heating rate of 5°C / min in an argon atmosphere for activation, and activating it for X3 h, where X1=900 and X3=2; then cooling it to room temperature in the furnace to obtain a calcined product;

[0241] S5. The calcined product is pickled with dilute hydrochloric acid at a concentration of 2 mol / L for 3 h; then filtered and washed with deionized water until neutral, and dried at 60° C. for 12 h to obtain an activated carbon electrode material.

[0242] The specific capacitance of the activated carbon electrode material obtained is YF / g, where Y and X1, X2, X3 and X4 satisfy the following relationship:

[0243] Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4

[0244] +0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where X1=900, X2=24, X3=2, X4=4.

[0245] Test Example 1:

[0246] The activated carbon electrode material in Examples 1-16 was subjected to an electrochemical (specific capacitance) test, and the specific steps were as follows: the prepared activated carbon electrode material was ground through a 300 mesh sieve, and the obtained activated carbon powder was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 in NMP, stirred and ground into a slurry, coated on a 1cm×1cm nickel foam substrate, and placed in a 60°C drying oven for 8h. The constant current charge and discharge test was analyzed by a CHI660E electrochemical workstation. In a three-electrode system, a saturated calomel electrode (SCE) and platinum foil (Pt) were used as reference electrodes and auxiliary electrodes, respectively, and a 6mol / L potassium hydroxide solution was used as an electrolyte. The test window of the activated carbon supercapacitor was -1.0-0V. The test results are shown in Table 2.

[0247] Table 2

[0248]

[0249]

[0250] At the same time, the equations listed in the embodiments are calculated, and the capacitance values ​​of each embodiment are calculated as follows (unit: F / g):

[0251] Example 1: 366.552, Example 2: 314.971, Example 3: 234.2, Example 4: 210.66, Example 5: 338.512, Example 6: 321.728, Example 7: 295.678, Example 8: 309.078, Example 9: 277.718, Example 10: 260.004, Example 11: 182.2, Example 12: 181.63, Example 13: 175.412, Example 14: 185.275, Example 15: 173.7, Example 16: 173.313.

[0252] The above measured capacitance values ​​are fitted with the calculated capacitance values, and the results are as follows: Figure 6 (activator is KOH), Figure 7 (The activator is NaOH), Figure 8 (activator is K2CO3), Fig. 9 (The activating agent is Na2CO3). Figure 6-9The following are scatter plots comparing the predicted values ​​and actual values ​​of the formula under different activators, where the diagonal line (y=x) represents the ideal situation where the predicted value is equal to the actual value. The results show that most of the data points are distributed near the diagonal line, indicating that the model has a high fitting accuracy. In addition, the color of the data points reflects the impact of the experimental conditions on the predicted values ​​(such as changes in experimental parameters). Although some data points deviate slightly from the diagonal line, the overall error is small, indicating that the model can describe the experimental data well. The R 2 They are 0.9566, 0.9534, 0.9913 and 0.9872 respectively, which fully demonstrates the rationality of the fitting results.

[0253] As shown in Table 2, KOH is the activator with the best activation effect. The activated carbon electrode material prepared by KOH has a more ideal morphology, structure and specific capacitance electrochemical performance, but it has the highest cost, strong corrosiveness and will cause pollution. The lignite-based supercapacitor activated carbon electrode material prepared by NaOH in Example 2 has a low micropore ratio in structure, a certain degree of retention in composition, and relatively good electrochemical performance. The electrochemical performance of the lignite-based supercapacitor activated carbon electrode material prepared by K2CO3 and Na2CO3 in Examples 3 and 4 will be significantly lower than that of the activated carbon electrode material in Examples 1 and 2, but its reaction is mild and causes little pollution.

[0254] Each activator has its own advantages and disadvantages and suitable conditions. In practical applications, it needs to be selected according to different needs.

[0255] Test Example 2:

[0256] Long cycle stability is a key performance indicator of supercapacitors in practical applications, such as Fig.10 As shown in the figure, the lignite-based activated carbon electrode material prepared in Example 1 exhibits excellent cycle stability. -1 After 10,000 cycles at a current density of 1.5 Å, the initial capacitance was still 93.3% of that after 10,000 cycles. After 10,000 cycles, the Coulombic efficiency remained at around 98.5%, indicating the high reversibility of the electrode. Fig.10 As shown in the attached figure, the GCD curves of the first three cycles and the last three cycles of the carbon electrode are also very similar, which once again emphasizes its stability.

[0257] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a lignite-based supercapacitor activated carbon electrode material, characterized in that: The following steps are involved: S1. The raw lignite powder is pickled with hydrochloric acid at a concentration of 1-5 mol / L for X2 h, and then washed with water and dried; then pickled with hydrofluoric acid at a concentration of 5-30wt% for X2 h, and then washed with water and dried; then heated and deoxidized with a calcium phosphate solution at a concentration of 1-2 mol / L, and then washed with water and dried to obtain pretreated lignite; S2, stirring and mixing the pretreated lignite, alkaline activator and deionized water in a mass ratio of 1:X4:5-10 to obtain a mixture; S3, activating the mixture under an inert atmosphere at a temperature of X1°C and an activation time of X3 h; then cooling the mixture to room temperature to obtain a calcined product; S4, washing the calcined product with dilute hydrochloric acid, washing with water, and drying to obtain the lignite-based supercapacitor activated carbon electrode material; The specific capacitance of the lignite-based supercapacitor activated carbon electrode material is YF / g, and Y and X1, X2, X3 and X4 satisfy the following relationship: Y=a+b·X1+c·X2+d·X3+e·X4–f·X1·X2+g·X1·X3+h·X1·X4+i·X2·X3+j·X2·X4+k·X3·X4 –l·X1 2 –m·X2 2 –n·X3 2 –o·X4 2 ; Among them, -12498.70833≤a≤-8849.075, 15.54675≤b≤24.2525, 0≤c≤74.67875, 305.425≤d≤841.425,821.57333≤e≤1312.7,-0.001167≤f≤0.02375, -0.109≤g≤0.243, -0.224≤h≤0.11, -0.81667≤i≤0.6125, -3.825≤j≤0.62917, -49.5≤k≤0.2, 0.01086≤l≤0.016075, 0≤m≤0.80698, 40.42≤n≤138.6, 42.17667≤o≤177.5; 650≤X1≤900, 20≤X2≤28, 0.5≤X3≤3.5, 2≤X4≤7.

5.

2. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 1, characterized in that: The alkaline activator is one of KOH, NaOH, K2CO3, and Na2CO3.

3. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 2, characterized in that: When the alkaline activator is KOH, Y=-12498.70833+24.2525X1+74.67875X2+505.95333X3+905.95X4–0.02375X1·X2+0.061X1·X3+0.11X1·X4+0.6125X2·X3–3.825X2·X4–34.9X3·X4–0.016075X1 2 –0.80698X2 2 –99.44667X3 2 –82.04667X4 2 , among which, 700≤X1≤800, 20≤X2≤28, 1.5≤X3≤2.5, 4.5≤X4≤5.

5.

4. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 2, characterized in that: When the alkaline activator is NaOH, Y=-12493.07+24.07743X1+2.29458X2+357.18667X3+821.57333X4+0.001167X1·X2+0.243X1·X3–0.224X1·X4–0.816667X2·X3+0.629167X2·X4–49.5X3·X4–0.014203X1 2 –0.13876X2 2 –82.67667X3 2 –42.17667X4 2 , among which, 750≤X1≤850, 20≤X2≤28, 0.5≤X3≤1.5, 6.5≤X4≤7.

5.

5. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 2, characterized in that: When the alkaline activator is K2CO3, Y=-8849.075+15.54675X1+841.425X3+1312.7X4+0.018X1·X3–0.059X1·X4–6.5X3·X4–0.01086X1 2 – 138.6X3 2 – 177.5X4 2 , where 650≤X1≤750, X2=24, 2.5≤X3≤3.5, 2≤X4≤4.

6. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 2, characterized in that: When the alkaline activator is Na2CO3, Y=-11619.0675+22.80590X1+305.425X3+823.685X4–0.109X1·X3+0.017X1·X4+0.2X3·X4–0.013192X1 2 –40.42X3 2 –103.62X4 2 , where 800≤X1≤900, X2=24h, 2≤X3≤3, 3.5≤X4≤4.

5.

7. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 1, characterized in that: In step S1, the method for preparing the raw lignite powder comprises the following steps: crushing, grinding and sieving the lignite to obtain raw lignite powder; the lignite is Hebei Lingshou lignite; the ash content of the lignite is 27-30%.

8. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 1, characterized in that: In step S1, the heating temperature of the heating deoxidation is 60-80°C, and the deoxidation time is 20-28h.

9. The method for preparing the lignite-based supercapacitor activated carbon electrode material according to claim 1, characterized in that: In step S3, the inert gas is nitrogen or argon; and the temperature is raised to X1°C at a heating rate of 2-5°C / min; In step S4, the dilute hydrochloric acid pickling is carried out using hydrochloric acid with a concentration of 1-2 mol / L, and the pickling time is 2-5 hours.

10. A lignite-based supercapacitor activated carbon electrode material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation process of coal-based ash-free porous carbon and application of coal-based ash-free porous carbon in supercapacitor

    CN121202126A

  • Preparation method and application of high-density graded porous carbon material

    CN121405090A

  • Lignin-based supercapacitor carbon and preparation method and application thereof

    CN122187035A

  • Lignin-based supercapacitor carbon and preparation method and application thereof

    CN122187035B